Teachers Making Sense of School Assessment through Social and Cultural Frameworks - Urszula Opłocka (University of Lower Silesia, 2013)
Using the network metaphor, we could call education a hub in which various cultural influences meet and clash and affect education in different ways and with varying strength. This educational hub on one hand "adapts to" changes taking place in everyday life, and on the other hand resists those changes due to classification and institutionalization. As a result, the aims of educational changes, such as new forms of school assessment, are subject to many different influences. Therefore, the emerging models are not homogenous, and most of them are rather a catalogue of propositions, which are seldom matched by reality. This effect is strengthened by the multiplicity of discourses which make choice possible, and which do not require a person to be unconditionally faithful to her/his option of choice. What happens in the classroom is a result of knowing or not knowing this catalogue of propositions and individual choices, and of the compliance, opportunism or even creativity in relation to the laws and regulations regulating teachers' work. Therefore teachers pedagogies of assessment are highly individual, while at the same time internally consistent. The goal of this article is to describe how official pedagogical discourse and teachers themselves make sense of assessment, and to identify some sources of this variability of assessment pegagogies.